Music training and empathy positively impact adults’ sensitivity to infant distress - Parsons, Christine E.; Young, Katherine S.; Jegindø, Else-Marie E.; Vuust, Peter; Stein, Alan; Kringelbach, Morten L. (Frontiers in Psychology, 2014)
Crying is the most powerful auditory signal of infant need. Adults’ ability to perceive and respond to crying is important for infant survival and in the provision of care. This study investigated a number of listener variables that might impact on adults’ perception of infant cry distress, namely parental status, musical training and empathy. Sensitivity to infant distress was tested using a previously validated task, which experimentally manipulated distress by varying the pitch of infant cries. Parents with musical training showed a significant advantage on this task when compared with parents without. The extent of the advantage was correlated with the amount of self-reported musical training. For non-parents, individual differences in empathy were associated with task performance, with higher empathy scores corresponding to greater sensitivity to infant distress. We suggest that sensitivity to infant distress can be impacted by a number of listener variables, and may be amenable to training.